Composition having magnetostrictive properties and cured product thereof
Patent Information
- Application Number
- CN202280016045.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-03-01
- Filing Date
- 2022-03-01
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2042-03-01
AI Technical Summary
[0027]根据本发明,能够提供具有磁致伸缩特性的新型磁致伸缩复合材料。
Smart Images

Figure CN116897399B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to compositions having magnetostrictive properties and their cured forms.
[0002] This application claims priority based on Japanese Patent Application No. 2021-031516, filed in Japan on March 1, 2021, the contents of which are incorporated herein by reference. Background Technology
[0003] Magnetostrictive materials are materials that deform slightly when a magnetic field is applied; the phenomenon of this deformation is called "magnetostriction".
[0004] Conversely, applying force to a magnetostrictive material and deforming it causes a change in the magnetic field inside the material, known as contramagnetic stricture. This change in magnetic field caused by contramagnetic stricture can be utilized in sensors and vibration-based power generation. Magnetostriction is a property of strongly magnetic materials. In strongly magnetic materials such as Fe (iron), Co (cobalt), and Ni (nickel), it can change by a proportion of approximately 0.01 to 0.0001% relative to the initial shape. Furthermore, Terfenol-D (Fe-Dy (dysprosium)-Tb (terbium) alloy), Galfenol (Fe-Ga (gallium) alloy), and Fe-Co alloy are known as magnetostrictive materials with high magnetostrictive properties, also known as supermagnetostriction.
[0005] As a magnetostrictive material, a composite reinforced magnetostrictive composite material has been proposed in the past, which is obtained by embedding wire formed of iron-based magnetostrictive alloy as a filler material into the parent material (matrix).
[0006] Specifically, an FeCo fiber reinforced composite material is disclosed, which is formed by unidirectionally arranging FeCo fibers as filler in a mold, and then allowing epoxy resin masterbatch to flow into the mold and cure it under a specified stress (see Patent Document 1).
[0007] Existing technical documents
[0008] Patent documents
[0009] Patent Document 1: Japanese Patent Application Publication No. 2017-163119 Summary of the Invention
[0010] The problem that the invention aims to solve
[0011] However, in the composite reinforced magnetostrictive composite material described in Patent Document 1, multiple wires formed of iron-based magnetostrictive alloys must be aligned and arranged in the same direction, which requires complicated operations.
[0012] In addition, as mentioned above, magnetostrictive materials whose surrounding magnetic field changes due to stress loads are expected to be used as environmental power generation or stress sensors based on repeated stress loads.
[0013] However, magnetostrictive materials with high magnetostrictive properties, such as Terfenol-D and Galfenol, are inherently brittle and therefore have difficulty withstanding repeated stress loads. While Fe-Co alloys, with slightly lower magnetostrictive properties, exhibit slightly better mechanical properties, their fatigue characteristics remain insufficient.
[0014] The present invention was made in view of the above circumstances, and the objective is to provide a novel magnetostrictive composite material with magnetostrictive properties.
[0015] Methods for solving problems
[0016] The inventors of this application have developed a novel magnetostrictive composite material in which the magnetostrictive material is dispersed in a base material cured by free radical polymerization, using powdered magnetostrictive material. Specifically, to solve the aforementioned problems, this invention employs the following configuration.
[0017] [1] A composition having magnetostrictive properties, comprising (P) component: a compound containing polymerizable groups; (M) component: a powdered magnetostrictive material; and (R) component: a free radical polymerization initiator.
[0018] [2] The composition as described in [1], wherein the aforementioned (M) component is a group of particles with an average particle size of 5 μm or more and 50 μm or less formed from an iron-based magnetostrictive alloy.
[0019] [3] The composition as described in [1] or [2], wherein the content of the aforementioned (M) component is 40% to 60% by volume relative to the total volume of the aforementioned (P) component, the aforementioned (M) component and the aforementioned (R) component, and the composition has negative magnetostrictive properties.
[0020] [4] The composition as described in any one of [1] to [3], wherein the content of the aforementioned (R) component is 0.01 parts by mass or more and 20 parts by mass or less relative to 100 parts by mass of the aforementioned (P) component.
[0021] [5] The composition of any one of [1] to [4], wherein the aforementioned (P) component is a thermosetting resin containing polymerizable unsaturated double bonds.
[0022] [6] The composition of any one of [1] to [5], wherein the aforementioned (P) component is a thermosetting elastomer with a glass transition temperature of -130°C to -5°C.
[0023] [7] The composition as described in [6], wherein the aforementioned thermosetting elastomer is urethane (meth) acrylate.
[0024] [8] The composition as described in [7], wherein the aforementioned thermosetting elastomer is a urethane (meth) acrylate with a weight average molecular weight of 2,000 to 30,000, obtained by reacting a polycaprolactone polyol, an aliphatic or alicyclic diisocyanate with a number average molecular weight of 300 to 900 with a hydroxyl-containing (meth) acrylate.
[0025] [9] A cured product obtained by curing any one of the compositions described in [1] to [8].
[0026] The effects of the invention
[0027] According to the present invention, a novel magnetostrictive composite material with magnetostrictive properties can be provided. Attached Figure Description
[0028] [ Figure 1 This is a schematic diagram illustrating the evaluation method for magnetostrictive properties in this embodiment.
[0029] [ Figure 2 This is a top-down view of the (M) component particles dispersed in the solidified sample before and after the application of a magnetic field. Figure 2 In the diagram, the arrow (in the z-axis direction) indicates the direction in which the magnetic field is applied. Figure 2 (A) shows the state of the (M) component particles dispersed in the solidified sample before the magnetic field is applied. Figure 2 (B) shows the state of (M) component particles dispersed in the solidified sample after a magnetic field is applied (positive magnetostriction). Figure 2 (C) shows the state of (M) component particles dispersed in the solidified sample after a magnetic field is applied (negative magnetostriction).
[0030] [ Figure 3 [1] is a graph showing the shape changes of (M) component particles dispersed in the cured sample as a result of the curing of the composition of Example 6 with the application of a magnetic field. The vertical axis represents magnetostriction, λ (ppm). The horizontal axis represents magnetic flux density, B (mT).
[0031] [ Figure 4 This is a graph showing the shape changes of (M) component particles dispersed in the cured sample as a result of the curing of the composition of Example 3 with the application of a magnetic field. The vertical axis represents magnetostriction, λ (ppm). The horizontal axis represents magnetic flux density, B (mT). Detailed Implementation
[0032] (A composition with magnetostrictive properties)
[0033] The composition of this embodiment is a magnetostrictive composite material with magnetostrictive properties, which contains (P) component: a compound containing polymerizable groups, (M) component: a powdered magnetostrictive material, and (R) component: a free radical polymerization initiator.
[0034] The magnetostrictive properties of this magnetostrictive composite material refer at least to: the property of dimensional change when a magnetic field is applied; and the property of change of the magnetic field inside the material when pressure is applied.
[0035] In the previous property, the phenomenon of elongation in the same direction when a unidirectional magnetic field is applied is called "positive magnetostriction", and the phenomenon of shortening in the same direction is called "negative magnetostriction".
[0036] The composition of this embodiment can exhibit both positive and negative magnetostriction.
[0037] The form of the composition in this embodiment is not particularly limited, but as a preferred form, a powdered magnetostrictive material dispersed in the composition can be cited.
[0038] In addition, the composition of this embodiment may be in the form of a dispersion or solution, or it may be in the form of powder or block.
[0039] <(P) Components: Compounds containing polymeric groups>
[0040] When the composition is cured, the (P) component polymerizes under the action of the (R) component, which can form the base material (matrix) of the cured product.
[0041] The term "polymerizable group" in component (P) refers to a group that enables a compound containing a polymerizable group to polymerize through free radical polymerization or the like. For example, it refers to a group containing multiple bonds between carbon atoms, such as polymerizable unsaturated double bonds.
[0042] (P) The “polymerizable group” in the component is not particularly limited, but is preferably a free radical polymerizable group.
[0043] The multiple bonds between carbon atoms can be polymeric carbon-carbon double bonds or polymeric carbon-carbon triple bonds, preferably polymeric carbon-carbon double bonds. Examples of polymeric carbon-carbon double bonds include methacryloyl and acryloyl groups.
[0044] (P) The polymeric groups contained in the component may be one or more.
[0045] From the viewpoint of effectively utilizing the magnetostrictive properties, the (P) component is preferably a thermosetting resin, and more preferably a thermosetting resin containing polymerizable unsaturated double bonds.
[0046] The number of polymeric groups contained in component (P) can be appropriately determined according to its intended use, etc.
[0047] For example, as component (P), compounds containing 1 to 6 polymeric groups can be cited. From the viewpoint of durability under repeated stress loads and low elastic modulus, compounds containing 1 to 5 polymeric groups are preferred, compounds containing 1 to 4 polymeric groups are more preferred, and compounds containing 1 or 2 polymeric groups are particularly preferred.
[0048] Furthermore, from the viewpoints of durability under repeated stress loads and low elastic modulus, component (P) is preferably a thermosetting resin with a slightly lower glass transition temperature, and more preferably a thermosetting resin with a glass transition temperature of 0°C or less.
[0049] In this specification and claims, "glass transition temperature" refers to the value measured using the test method in accordance with JIS K 7244-1:1998 (ISO 6721-1:1994).
[0050] Of the above, considering durability under repeated stress loads and low elastic modulus, a thermosetting elastomer is preferred as component (P). When it is a thermosetting elastomer, a low elastic modulus is easily achieved after curing.
[0051] As component (P), more preferably, it is a thermosetting elastomer with a glass transition temperature of 0°C or less; even more preferably, it is a thermosetting elastomer with a glass transition temperature of -130°C or more but less than 5°C; particularly preferably, it is a thermosetting elastomer with a glass transition temperature of -100°C or more but less than 5°C; and most preferably, it is a thermosetting elastomer with a glass transition temperature of -50°C or more but less than 10°C.
[0052] If the glass transition temperature of the thermosetting elastomer, which is component (P), is below the upper limit of the aforementioned preferred range, it is easy to achieve a low elastic modulus when the cured product is made. On the other hand, if it is above the lower limit of the aforementioned preferred range, the strength of the cured product can be improved.
[0053] Thermosetting Elastomers
[0054] As thermosetting elastomers, examples include resin-based elastomers, with urethane (meth)acrylates being a preferred example.
[0055] This urethane (meth)acrylate can be synthesized by an addition reaction of a polyol ((O) component), a polyisocyanate compound ((I) component), and a hydroxyl-containing (meth)acrylate. For example, it can be synthesized by performing a known urethane esterification reaction.
[0056] Here, "(meth)acrylate" is a concept that includes both methacrylate and acrylate, referring to either methacrylate or acrylate.
[0057] The polyol ((O) component) is a compound having two or more hydroxyl groups (-OH). There are no particular limitations on the (O) component; substances commonly used in the manufacture of polyurethane resins can be used without particular restriction.
[0058] The (O) component can be an aliphatic polyol or an aromatic polyol. Alternatively, the (O) component can be a low-molecular-weight polyol or a high-molecular-weight polyol.
[0059] In this specification and claims, "aliphatic" is a relative concept compared to "aromatic," defined as representing non-aromatic groups, non-aromatic compounds, etc. "Alicyclic" refers to non-aromatic groups, non-aromatic compounds, and substances with cyclic structures.
[0060] Specific examples of low-molecular-weight polyols include ethylene glycol, 1,2-propanediol, 1,2-butanediol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, neopentanediol, alkane diols with 7 to 22 carbon atoms, diethylene glycol, triethylene glycol, dipropylene glycol, 3-methyl-1,5-pentanediol, 2-ethyl-2-butyl-1,3-propanediol, alkane-1,2-diols with 17 to 20 carbon atoms, and 1,3-cyclohexanediol. Diols such as 1,4-cyclohexanediol, 1,4-cyclohexanediol, hydrogenated bisphenol A, 1,4-dihydroxy-2-butene, 2,6-dimethyl-1-octen-3,8-diol, and bisphenol A; triols such as glycerol and trimethylolpropane; tetramethylolmethane (pentaerythritol) and diglycerol; pentols such as xylitol; hexaols such as sorbitol, mannitol, allitol, idotitol, eurythritol, atroitol, inositol, and dipentaerythritol; septols such as avocadool; and octols such as sucrose. Among these, glycols with a number average molecular weight of 50 to 300 are preferred, and ethylene glycol, diethylene glycol, triethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, and neopentanediol are more preferred. These can be used alone or in combination of two or more.
[0061] Specific examples of high molecular weight polyols include phenolic resins, resins containing a hydroxystyrene backbone, polyester polyols, polyether polyols, polyether ester polyols, polyesteramide polyols, acrylic polyols, polycarbonate polyols, polyhydroxyalkane, polyurethane polyols, polycaprolactone polyols, and vegetable oil-based polyols. Among these, polycaprolactone polyols are preferred. These can be used alone or in combination of two or more. The number average molecular weight of the high molecular weight polyol is preferably 300 to 2000, more preferably 300 to 1500, and even more preferably 300 to 900.
[0062] As the polyisocyanate compound (component (I)), aliphatic diisocyanates, alicyclic diisocyanates, aromatic diisocyanates, or mixtures thereof can be used. As an aliphatic diisocyanate, hexamethylene diisocyanate is preferred.
[0063] As the aforementioned alicyclic diisocyanate, preferred options include hydrogenated xylene diisocyanate, isophorone diisocyanate, methyl cyclohexane 1,3-diisocyanate, methyl cyclohexane 1,4-diisocyanate, norbornene diisocyanate, and dicyclohexylmethane-4,4'-diisocyanate.
[0064] As the aforementioned aromatic diisocyanate, 4,4-diphenylmethane diisocyanate is preferred.
[0065] Of these, component (I) is preferably an aliphatic or alicyclic diisocyanate.
[0066] These can be used individually or in combination of two or more.
[0067] A hydroxyl-containing (meth)acrylate has at least one hydroxyl group and at least one (meth)acryloyl group in one molecule.
[0068] Examples of hydroxyl-containing (meth)acrylates include, for example, unsaturated fatty acid hydroxyalkyl esters such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate; ε-caprolactone adducts of the aforementioned unsaturated fatty acid hydroxyalkyl esters (average addition molar number 1 to 10); polyethylene glycol (average addition molar number 1 to 10) mono(meth)acrylate, polypropylene glycol (average addition molar number 1 to 10) mono(meth)acrylate; pentaerythritol mono(meth)acrylate, ... Pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate; dipentaerythritol di(meth)acrylate, dipentaerythritol tri(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate; glycerol mono(meth)acrylate, diglycerol tri(meth)acrylate, diglycerol di(meth)acrylate; sorbitol mono(meth)acrylate, sorbitol di(meth)acrylate, sorbitol tri(meth)acrylate, sorbitol tetra(meth)acrylate, etc.
[0069] Among these, (meth)acrylates containing hydroxyl groups are preferably unsaturated fatty acid hydroxyalkyl esters.
[0070] These hydroxyl-containing (meth)acrylates can be used alone or in combination of two or more.
[0071] The weight-average molecular weight (Mw) of the thermosetting elastomer is preferably 2,000 to 30,000, more preferably 2,000 to 20,000, and even more preferably 3,000 to 10,000.
[0072] If the Mw of the thermosetting elastomer is above the lower limit of the aforementioned preferred range, it is easy to improve the strength when the cured product is made. On the other hand, if it is below the upper limit of the aforementioned preferred range, it is easy to achieve a low elastic modulus when the cured product is made.
[0073] In this specification and claims, the weight-average molecular weight (Mw) of thermosetting elastomers refers to the value converted from standard polystyrene by GPC determination.
[0074] Of the above, the thermosetting elastomer is preferably a polycaprolactone polyol, an aliphatic or alicyclic diisocyanate, or a hydroxyl-containing (meth)acrylate obtained by reacting them with a hydroxyl-containing (meth)acrylate, and a urethane (meth)acrylate with a weight average molecular weight of 2,000 to 30,000.
[0075] Polyfunctional (meth)acrylate compounds
[0076] In addition, as a (P) component, polyfunctional (meth)acrylate compounds can be used.
[0077] In this specification, "multifunctional" refers to having two or more functional groups. Multifunctional monomers include, for example, monomers having two functional groups, monomers having three functional groups, monomers having four functional groups, or monomers having even more functional groups. Multifunctional acrylates include diacrylates, triacrylates, and tetraacrylates. Additionally, multifunctional methacrylates include dimethacrylates, trimethacrylates, and tetramethacrylates.
[0078] Examples of multifunctional (meth)acrylate compounds include, for example, ethoxylated (3)trimethylolpropane triacrylate, ethoxylated (3)trimethylolpropane trimethacrylate, ethoxylated (6)trimethylolpropane triacrylate, ethoxylated (9)trimethylolpropane triacrylate, ethoxylated (15)trimethylolpropane triacrylate, ethoxylated (20)trimethylolpropane triacrylate, pentaerythritol triacrylate, pentaerythritol trimethacrylate, propoxylated (3)glyceryl triacrylate, propoxylated (3)glyceryl triacrylate, propoxylated (5.5)glyceryl triacrylate, propoxylated (3)trimethylolpropane triacrylate, and propoxylated... (6) Trimethylolpropane triacrylate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, tri-(2-hydroxyethyl)-isocyanurate triacrylate, tri-(2-hydroxyethyl)-isocyanurate trimethacrylate, EO-modified trimethylolpropane tri(meth)acrylate, PO-modified trimethylolpropane tri(meth)acrylate, EO, PO-modified trimethylolpropane tri(meth)acrylate and other 3-functional monomers; bistrimethylolpropane tetraacrylate, ethoxylated (4) pentaerythritol tetraacrylate, pentaerythritol tetra(meth)acrylate and other 4-functional monomers; dipentaerythritol pentaacrylate, dipentaerythritol hexaacrylate and other monomers with 5 or more functions.
[0079] (P) Components can be used alone or in combination of two or more.
[0080] <(M) Composition: Powdered magnetostrictive material>
[0081] (M) is a powdery material that deforms slightly when a magnetic field is applied.
[0082] The average particle size of the (M) component is preferably 5 μm or more and 50 μm or less, more preferably 5 μm or more and 40 μm or less, and even more preferably 5 μm or more and 30 μm or less.
[0083] If the average particle size of the particle group of component (M) is above the lower limit of the aforementioned preferred range, good dispersibility is easily obtained; on the other hand, if it is below the upper limit of the aforementioned preferred range, good surface smoothness is easily obtained.
[0084] In this specification and claims, the average particle size of the particle group of component (M) is expressed as the volume average particle size measured using the test method of particle size analysis - laser diffraction and scattering as specified in JIS Z8825:2013.
[0085] As a component (M), examples include groups of metal particles containing Ni, Fe-Ni alloys, Fe-Co alloys, Fe-Al alloys, Fe-Ga-Al alloys, Fe-Dy-Tb alloys, or Fe-Ga alloys.
[0086] Among these, the (M) component preferably includes an iron-based magnetostrictive alloy. As an iron-based magnetostrictive alloy, Fe-Co alloys, Fe-Ga-Al alloys, Fe-Dy-Tb alloys, and Fe-Ga alloys are preferred, and Fe-Co alloys are even more preferred.
[0087] Specific examples of Fe-Co alloys can be cited. (100at%-x-y) -Co x -V y (In the formula, x = 30-90 at% and y = 0-10 at%).
[0088] Specific examples of Fe-Al alloys can be cited as Fe (100at%-x) -Al x (where x = 40-80 at%).
[0089] Specific examples of Fe-Ga-Al alloys can be given (Fe (100at%-x-y) -Ga x -Al y ) 100at%-z -C z (where x = 10–15 at% , y = 4–7 at% , and z = 0–2 at% ); (Fe (100at%-x-y) -Ga x -Al y ) 100at%-z -B z (In the formula, x = 10-15 at% , y = 4-7 at% , and z = 0-2 at% ).
[0090] The aforementioned specific examples of Fe-Ga-Al alloys are FeGaAl alloys containing C (carbon) or B (boron).
[0091] Examples of Fe-Dy-Tb alloys include Terfenol-D.
[0092] Examples of Fe-Ga alloys include Galfenol.
[0093] Component (M) can be used alone or in combination of two or more. Among the above, from the viewpoint of magnetostrictive properties and dispersion stability in the parent material, component (M) is preferably a group of particles containing iron-based magnetostrictive alloys with an average particle size of 5 μm to 50 μm.
[0094] <(R) Component: Free radical polymerization initiator>
[0095] Component (R) is a free radical polymerization initiator. During the curing of the composition, it interacts with the polymerizable groups of component (P) to promote the polymerization reaction and contribute to the formation of the matrix of the cured product. Examples of components (R) include thermal free radical polymerization initiators and photofree radical polymerization initiators.
[0096] Thermal free radical polymerization initiators
[0097] Examples of thermal free radical polymerization initiators include peroxides and azo polymer initiators.
[0098] Peroxides used as initiators of thermal free radical polymerization include, for example, ketone peroxides, peroxy ketals, hydroperoxides, dialkyl peroxides, and peroxy esters.
[0099] Specifically, examples of such peroxides include acetyl peroxide, dicumyl peroxide, tert-butyl peroxide, tert-butyl cumyl peroxide, propionyl peroxide, benzoyl peroxide (BPO), 2-chlorobenzoyl peroxide, 3-chlorobenzoyl peroxide, 4-chlorobenzoyl peroxide, 2,4-dichlorobenzoyl peroxide, 4-bromomethylbenzoyl peroxide, lauroyl peroxide, potassium persulfate, diisopropyl peroxide, tetrahydronaphthalene hydroperoxide, 1-phenyl-2-methylpropyl-1-hydroperoxide, tert-butyl pertriphenylacetate, tert-butyl hydroperoxide, tert-butyl performate, tert-butyl peracetate, tert-butyl perbenzoate, tert-butyl perphenylacetate, tert-butyl perphenylacetate, tert-butyl per4-methoxyacetate, and tert-butyl perN-(3-tolyl)carbamate.
[0100] Among the aforementioned peroxides, commercially available products manufactured by Nippon Yushu Co., Ltd., under the trade names "Percumyl (registered trademark)," "Perbutyl (registered trademark)," "Peroyl (registered trademark)," and "Perocta (registered trademark)," can be used, for example.
[0101] Examples of azo-based polymerization initiators used as thermal free radical polymerization initiators include 2,2'-azobispropane, 2,2'-dichloro-2,2'-azobispropane, 1,1'-azo(methylethyl)diacetate, 2,2'-azobis(2-amidinylpropane) hydrochloride, 2,2'-azobis(2-aminopropane) nitrate, 2,2'-azobisisobutane, 2,2'-azobisisobutylamide, 2,2'-azobisisobutyronitrile, and 2,2'-... methyl azobis-2-methylpropionate, 2,2'-dichloro-2,2'-azobisbutane, 2,2'-azobis-2-methylbutyronitrile, dimethyl 2,2'-azobis(2-methylpropionate) (2,2'-azobisisobutyronate), 1,1'-azobis(1-methylbutyronitrile-3-sulfonate), 2-(4-methylphenylazo)-2-methylmalonadionitrile 4,4'-azobis-4-cyanopentanoic acid, 3,5-dihydroxymethylphenylazo 2-Allylmalonidium, 2,2'-azobis-2-methylpentanonitrile, dimethyl 4,4'-azobis-4-cyanopentanoate, 2,2'-azobis-2,4-dimethylpentanonitrile, 1,1'-azobiscyclohexanenitrile, 2,2'-azobis-2-propylbutanonitrile, 1,1'-azobiscyclohexanenitrile, 2,2'-azobis-2-propylbutanonitrile, 1,1'-azobis-1-chlorophenylethane, 1,1'-azobis-1-cyclohexaneformonitrile, 1,1 '-Azobis-1-cycloheptanenitrile, 1,1'-Azobis-1-phenylethane, 1,1'-Azobisisopropylbenzene, ethyl 4-nitrophenylazobenzylcyanoacetate, phenylazodiphenylmethane, phenylazotriphenylmethane, 4-nitrophenylazotriphenylmethane, 1,1'-Azobis-1,2-diphenylethane, poly(bisphenol A-4,4'-azobis-4-cyanovalerate), poly(tetraethylene glycol-2,2'-azobisisobutyrate), etc.
[0102] Photoradical polymerization initiators
[0103] Examples of photoradical polymerization initiators include: 1-hydroxycyclohexylphenyl ketone, 2-hydroxy-2-methyl-1-phenylpropane-1-one, 1-[4-(2-hydroxyethoxy)phenyl]-2-hydroxy-2-methyl-1-propane-1-one, 1-(4-isopropylphenyl)-2-hydroxy-2-methylpropane-1-one, 1-(4-dodecylphenyl)-2-hydroxy-2-methylpropane-1-one, 2,2-dimethoxy-1,2-diphenylethane-1-one, bis(4-dimethylaminophenyl)one, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropane-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butane-1-one, 1- [9-Ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]acetone-1-(o-acetyl oxime), 2,4,6-trimethylbenzoyl diphenylphosphine oxide, 4-benzoyl-4'-methyldimethyl sulfide, 4-dimethylaminobenzoic acid, methyl 4-dimethylaminobenzoate, ethyl 4-dimethylaminobenzoate, butyl 4-dimethylaminobenzoate, 4-dimethylamino-2-ethylhexylbenzoic acid, 4-dimethylamino-2-isopentylbenzoic acid, benzyl-β-methoxyethyl ketal, benzyl dimethyl ketal, 1-phenyl-1,2-propanedione-2-(o-ethoxycarbonyl) oxime, methyl o-benzoylbenzoate, 2,4-diethylthioxanone, 2-chlorothioxanone, 2,4-dimethyl... Thioxanone, 1-chloro-4-propoxythioxanone, thioxanone, 2-chlorothioxanone, 2,4-diethylthioxanone, 2-methylthioxanone, 2-isopropylthioxanone, 2-ethylanthraquinone, octamethylanthraquinone, 1,2-benzanthraquinone, 2,3-diphenylanthraquinone, azobisisobutyronitrile, benzoyl peroxide, cumene peroxide, 2-mercaptobenzimidazole, 2-mercaptobenzoxazole, 2-mercaptobenzothiazole, 2-(o-chlorophenyl)-4,5-diphenylimidazolium dimer, 2-(o-chlorophenyl)-4,5-di(methoxyphenyl)imidazolium dimer, 2-(o-fluorophenyl)-4,5-diphenylimidazolium dimer, 2-(o-methoxyphenyl)-4,5-diphenylimidazolium dimer, 2-(p-methoxyphenyl)-4,5-diphenylimidazolium dimer Polymers, 2,4,5-triarylimidazolium dimers, benzophenone, 2-chlorobenzophenone, 4,4'-bis(dimethylamino)benzophenone (i.e., michalcone), 4,4'-bis(diethylamino)benzophenone (i.e., ethyl michalcone), 4,4'-dichlorobenzophenone, 3,3-dimethyl-4-methoxybenzophenone, benzoin, benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin n-butyl ether, benzoin isobutyl ether, benzoin tert-butyl ether, acetophenone, 2,2-diethoxyacetophenone, p-dimethylacetophenone, p-dimethylaminoacetophenone, dichloroacetophenone, trichloroacetophenone, p-tert-butylacetophenone, p-dimethylaminoacetophenone, p-tert-butyltrichloroacetophenone, p-tert-butyldichloroacetophenone, α,α-Dichloro-4-phenoxyacetophenone, thioxanthone, 2-methylthioxanthone, 2-isopropylthioxanthone, dibenzocycloheptanone, pentyl 4-dimethylaminobenzoate, 9-phenylacridinium, 1,7-bis-(9-acridyl)heptane, 1,5-bis-(9-acridyl)pentane, 1,3-bis-(9-acridyl)propane, p-methoxytriazine, 2,4,6-tris(trichloromethyl)triazine, 2-methyl-4,6-bis(trichloromethyl)triazine, 2-[2-(5-methylfuran-2-yl)vinyl]-4,6-bis(trichloromethyl)triazine, 2-[2-(furan-2-yl)vinyl]-4,6-bis(trichloromethyl)triazine, 2-[2-(4-diethylamino-2-methylphenyl)vinyl]-4,6-bis(trichloromethyl)triazine Examples of triazine compounds include 2-[2-(3,4-dimethoxyphenyl)vinyl]-4,6-bis(trichloromethyl)triazine, 2-(4-methoxyphenyl)-4,6-bis(trichloromethyl)triazine, 2-(4-ethoxystyryl)-4,6-bis(trichloromethyl)triazine, 2-(4-butoxyphenyl)-4,6-bis(trichloromethyl)triazine, 2,4-bis-trichloromethyl-6-(3-bromo-4-methoxy)phenyltriazine, 2,4-bis-trichloromethyl-6-(2-bromo-4-methoxy)phenyltriazine, 2,4-bis-trichloromethyl-6-(3-bromo-4-methoxy)styrylphenyltriazine, and 2,4-bis-trichloromethyl-6-(2-bromo-4-methoxy)styrylphenyltriazine.
[0104] Among the aforementioned photoradical polymerization initiators, commercially available products such as "IRGACURE OXE02", "IRGACURE OXE01", "IRGACURE 369", "IRGACURE 651", "IRGACURE 907" (all trade names, manufactured by BASF) and "NCI-831" (trade name, manufactured by ADEKA Co., Ltd.) can be used.
[0105] Component (R) can be used alone or in combination of two or more. Preferably, it is a thermal free radical polymerization initiator, and more preferably an azo polymerization initiator.
[0106] The total content of component (P), component (M) and component (R) in the composition of this embodiment is preferably 80% by volume or more, more preferably 90% by volume or more, even more preferably 95% by volume or more, and may also be 100% by volume. Particularly preferred is a composition consisting of component (P), component (M) and component (R).
[0107] In the composition of this embodiment, the content of component (M) is preferably 10% to 80% to 100% of the total volume (100% by volume) of component (P), component (M) and component (R), and more preferably 20% to 70% to 100% by volume.
[0108] When the content of component (M) is within the aforementioned preferred range, the composition can exhibit either positive or negative magnetostriction.
[0109] Furthermore, when the content of component (M) is above the lower limit of the aforementioned preferred range, it is more likely to exhibit magnetostrictive properties; on the other hand, when it is below the upper limit of the aforementioned preferred range, the strength of the cured material is further improved.
[0110] Furthermore, in the composition of this embodiment, from the viewpoint that the composition is prone to having negative magnetostrictive properties, the content of component (M) is preferably 40% to 60% to 100% of the total volume (100% by volume) of component (P), component (M) and component (R), and more preferably 45% to 55% to 100% by volume.
[0111] Thus, in the composition of this embodiment, by controlling the volume fraction of the powdered magnetostrictive material in the cured product to a specific ratio, although the detailed reason is not determined, it is believed that the magnetostrictive material particles magnetized by the application of a magnetic field attract each other, thus exhibiting negative magnetostrictive properties.
[0112] Furthermore, in the composition of this embodiment, the content of component (R) is preferably 0.01 parts by mass or more and 20 parts by mass or less, more preferably 0.1 parts by mass or more and 15 parts by mass or less, and even more preferably 0.5 parts by mass or more and 10 parts by mass or less, relative to 100 parts by mass of component (P) mentioned above.
[0113] When the content of component (R) is above the lower limit of the aforementioned preferred range, the polymerization reaction efficiency between components (P) is further improved. On the other hand, when it is below the upper limit of the aforementioned preferred range, the polymerization reaction is sufficiently promoted, and the strength of the cured product is further improved.
[0114] <Other Ingredients>
[0115] In addition to components (P), (M) and (R), the composition of this embodiment may contain other components as needed.
[0116] Other components besides (P), (M) and (R) components include, for example, solvents, surfactants, dispersants, defoamers, antioxidants, fragrances, plasticizers, etc.
[0117] [Preparation method of the composition]
[0118] The composition of this embodiment can be prepared by a manufacturing method having a step of mixing (P) component, (M) component, (R) component, and other components added as needed.
[0119] Alternatively, the composition of this embodiment can also be prepared by a manufacturing method having the following steps: a first step of mixing component (P) and component (R) to obtain a mixture (PR); and a second step of mixing the mixture (PR) obtained in the first step with component (M).
[0120] In the second step, the mixing ratio (volume ratio) of the mixture (PR) to the component (M) is preferably (M) component / mixture (PR) = 10 / 90 to 80 / 20, more preferably 20 / 80 to 70 / 30. By controlling the volume ratio of the mixture (PR) to the component (M) within the aforementioned preferred range, the composition can exhibit either positive or negative magnetostriction.
[0121] Furthermore, from the viewpoint of enabling the composition to exhibit negative magnetostriction, in the second step, the mixing ratio (volume ratio) of the mixture (PR) and the (M) component is preferably (M) component / mixture (PR) = 40 / 60 to 60 / 40, more preferably 45 / 55 to 55 / 45.
[0122] (cured material)
[0123] The cured product of this embodiment is obtained by curing the above-described (composition with magnetostrictive properties). The shape of the cured product is not particularly limited, and examples include plate-shaped, cylindrical, and prismatic shapes.
[0124] [Method for manufacturing cured products]
[0125] The cured product of this embodiment can be manufactured, for example, by a manufacturing method having a step of pouring the above-described composition into a mold of a predetermined shape and performing a heat curing process.
[0126] Thermosetting can be performed in one operation or in two or more operations.
[0127] As explained above, the composition of this embodiment is a magnetostrictive composite material containing (P) a compound comprising polymerizable groups, (M) a powdered magnetostrictive material, and (R) a free radical polymerization initiator, exhibiting magnetostrictive properties. In other words, it is a novel magnetostrictive composite material that uses a powdered material as the magnetostrictive material and disperses the magnetostrictive material in a base material cured by free radical polymerization. Therefore, unlike conventional methods where wires formed from iron-based magnetostrictive alloys are embedded as fillers in the base material (matrix), this method is less complex and allows for simpler operation.
[0128] Furthermore, in the composition of this embodiment, the polymeric compound constituting the parent material can be selected, thus enabling the provision of magnetostrictive composite materials obtained by combining magnetostrictive materials with various polymers.
[0129] As the aforementioned magnetostrictive composite material, for example, by combining the magnetostrictive material with a low elastic modulus polymer, it is possible to provide a magnetostrictive composite material that can withstand repeated stress loads.
[0130] Alternatively, the composition of this embodiment can also be used for applications such as composite material substrates. For example, by laminating fiber-reinforced plastics such as glass fiber reinforced plastics or carbon fiber reinforced plastics with sheets formed from the composition of this embodiment or their cured products and then curing them, it is possible to provide an FRP bulk with a magnetostrictive effect.
[0131] Furthermore, by controlling the mixing ratio of the polymeric compound constituting the parent material and the powdered magnetostrictive material in the composition of this embodiment, it is possible to provide a magnetostrictive composite material that exhibits not only positive magnetostriction (elongation in the direction of magnetic field application) but also negative magnetostriction (shortening in the direction of magnetic field application).
[0132] According to the composition of the above embodiments, compared with magnetostrictive materials alone, further improvements in the functions of environmental power generation and stress sensors can be expected when utilizing bending stress or bending vibration.
[0133] The composition described above is a material that elicits a certain response through external stimuli, and is therefore useful as a smart material.
[0134] Example
[0135] The present invention will be further described in detail below by way of examples, but the present invention is not limited to these examples.
[0136] <Preparation of the Composition>
[0137] When preparing the compositions of each example, the (P) component, (M) component, and (R) component shown below were used respectively.
[0138] • (P) Components: Compounds containing polymeric groups
[0139] Compound (P-1): A urethane acrylate (product name DA-800AU, Nippon Yu Co., Ltd.) is used as a thermosetting elastomer resin. The glass transition temperature of the cured product is -30°C.
[0140] Compound (P-1) is obtained by reacting polycaprolactone diol with isophorone diisocyanate and 2-hydroxyethyl acrylate, which have a number average molecular weight of 530. The weight average molecular weight of compound (P-1) is 5200.
[0141] Compound (P-2): Dipentaerythritol hexaacrylate (trade name KAYARADDPHA, Nippon Kayaku Co., Ltd.) is used as a thermosetting resin. The glass transition temperature of the cured product exceeds 250°C.
[0142] • (M) Composition: Powdered magnetostrictive material
[0143] Using Fe 49 Co 49 V2 (Epson Atmix Co., Ltd.). Average particle size is 8.0 ± 1.0 μm.
[0144] • (R) Component: Free radical polymerization initiator
[0145] Dimethyl 2,2'-azobis(2-methylpropionic acid) was used as a thermal free radical polymerization initiator.
[0146] (Example 1)
[0147] Add 3 parts by mass of component (R) to 100 parts by mass of compound (P-1) and dissolve it by stirring to obtain a homogeneous solution.
[0148] Next, component (M) was added in the manner shown in Table 1 by volume fraction, and the mixture was stirred to prepare a composition as a dispersion of powdered magnetostrictive material.
[0149] Volume fraction is the amount of Fe as a component (M). 49 Co 49 The density of V2 is set to 8.6 g / cm³. 3 The densities of compounds (P-1) and (R) were set to 1.0 g / cm³. 3 It was calculated.
[0150] (Examples 2-4)
[0151] Except for changing the volume fraction as shown in Table 1, the same procedure as in Example 1 was followed to prepare a composition as a dispersion of a powdered magnetostrictive material.
[0152] (Example 5)
[0153] Add 3 parts by mass of component (R) to 100 parts by mass of compound (P-2) and dissolve it by stirring to obtain a homogeneous solution.
[0154] Next, component (M) was added in the manner shown in Table 2 by volume fraction, and the mixture was stirred to prepare a composition as a dispersion of powdered magnetostrictive material.
[0155] Volume fraction is the amount of Fe as a component (M). 49 Co 49 The density of V2 is set to 8.6 g / cm³. 3 The densities of compounds (P-2) and (R) were set to 1.0 g / cm³. 3 It was calculated.
[0156] (Examples 6-8)
[0157] Except for the changes in volume fraction as shown in Table 2, the same procedure as in Example 5 was followed to prepare a composition as a dispersion of the powdered magnetostrictive material.
[0158] <Preparation of solidified samples>
[0159] The compositions of each example were poured into a 10mm×10mm×2mm mold.
[0160] Then, each mold was placed on a ceramic heating plate (CHP-170DF(As one)), and nitrogen was blown in while the mold was heat-cured at 80°C for 2 hours. After that, it was further heat-cured at 120°C for 1 hour to obtain the cured sample.
[0161] <Evaluation of Magnetostrictive Properties>
[0162] Figure 1 This is a schematic diagram illustrating the evaluation method for magnetostrictive properties in this embodiment.
[0163] Figure 1 In the middle, a solidified sample 20 is placed between a pair of electromagnets 10 and 10.
[0164] An orthogonal strain gauge 30 is attached to a 6 mm square area on the surface of the cured sample 20. An electromagnet 10 applies a magnetic field of -1 Tesla to +1 Tesla in a unidirectional (z-axis direction) direction that is horizontal relative to the surface of the cured sample 20. It should be noted that the direction that is horizontal relative to the surface of the cured sample 20 and orthogonal to the z-axis direction is defined as the x-axis direction.
[0165] The deformation state of the solidified sample 20 at this point was evaluated using a vibrating specimen magnetometer. The evaluation results are shown in Tables 1-2 and... Figures 2-4 .
[0166] [Table 1]
[0167]
[0168] [Table 2]
[0169]
[0170] Based on the results in Table 1, it was confirmed that the cured products obtained by curing the compositions of Examples 1 to 4 using compound (P-1) as component (P) showed "positive magnetostriction", while only the cured product obtained by curing the composition of Example 3 showed "negative magnetostriction".
[0171] Based on the results in Table 2, it was confirmed that the cured products obtained by curing the compositions of Examples 5 to 8 using compound (P-2) as component (P) all showed "positive magnetostriction".
[0172] Figure 2 This is a top-down view of the (M) component particles dispersed in the solidified sample before and after the application of a magnetic field.
[0173] Figure 2 In the diagram, the arrow (in the z-axis direction) indicates the direction in which the magnetic field is applied.
[0174] Figure 2 (A) shows the state of (M) component particles 20a dispersed in the solidified sample before the application of a magnetic field, which are roughly circular when viewed from above.
[0175] Figure 2 (B) shows the state of the (M) component particles dispersed in the cured sample after the application of a magnetic field. Compared with the state of (M) component particles 21b before the application of the magnetic field, after the application of the magnetic field, the (M) component particles 22b elongate in the direction of the applied magnetic field, and when viewed from above, they are approximately elliptical in shape with their major axis parallel to the z-axis. That is, the composition with such (M) component particles dispersed has positive magnetostrictive properties.
[0176] Figure 2 (C) shows the state of the (M) component particles dispersed in the cured sample after the application of a magnetic field. Compared with the state of (M) component particles 23c before the application of the magnetic field, after the application of the magnetic field, the (M) component particles 24c shorten in the direction of the applied magnetic field, and when viewed from above, they are approximately elliptical in shape with their major axis orthogonal to the z-axis. That is, the composition with such (M) component particles dispersed has negative magnetostrictive properties.
[0177] Figure 3 This is a graph showing the shape changes of (M) component particles dispersed in the cured sample as a result of the curing of the composition of Example 6 with the application of a magnetic field. The vertical axis represents magnetostriction, λ (ppm). The horizontal axis represents magnetic flux density, B (mT).
[0178] Regarding the composition of Example 6, positive magnetostrictive properties were confirmed in the cured sample, which expands in the z-axis direction (which is the direction of magnetic field application) and contracts in the x-axis direction (which is the direction orthogonal to the direction of magnetic field application) upon the application of a magnetic field.
[0179] Figure 4 This is a graph showing the shape changes of (M) component particles dispersed in the cured sample as a result of the curing of the composition of Example 3 with the application of a magnetic field. The vertical axis represents magnetostriction, λ (ppm). The horizontal axis represents magnetic flux density, B (mT).
[0180] Regarding the composition of Example 3, it was confirmed that the cured sample exhibited negative magnetostrictive properties, shrinking in the z-axis direction (which is the direction of magnetic field application) and showing slight elongation and contraction in the x-axis direction (which is the direction orthogonal to the direction of magnetic field application), when a magnetic field was applied.
[0181] The preferred embodiments of the present invention have been described above, but the present invention is not limited to these embodiments. Additions, omissions, substitutions, and other modifications can be made to the structure without departing from the spirit of the present invention. The present invention is not limited by the foregoing description, but only by the appended claims.
[0182] Explanation of reference numerals in the attached figures
[0183] 10 electromagnets, 20 cured samples, 30 strain gauges
Claims
1. A composition having magnetostrictive properties, comprising: (P) Component: A polyfunctional (meth)acrylate compound containing polymerizable groups, wherein, Compounds that are thermosetting elastomers are excluded; (M) Composition: Powdered magnetostrictive material; and (R) Component: Azo polymer initiator used as a free radical polymerization initiator.
2. The composition of claim 1, wherein, The (M) component is a group of particles with an average particle size of 5 μm to 50 μm formed from iron-based magnetostrictive alloys.
3. The composition of claim 1, wherein, The content of component (M) is 10% to 80% by volume relative to the total volume of component (P), component (M), and component (R). The composition has negative magnetostrictive properties.
4. The composition of claim 1, wherein, The content of component (R) is 0.01 parts by mass or more and 20 parts by mass or less, relative to 100 parts by mass of component (P).
5. The composition of claim 1, wherein, The (P) component is at least one selected from the group consisting of tri(meth)acrylate, tetra(meth)acrylate, penta(meth)acrylate and hexa(meth)acrylate.
6. The composition of claim 5, wherein, The glass transition temperature of the cured product of component (P) exceeds 250°C.
7. A cured product obtained by curing the composition according to any one of claims 1 to 6.
Citation Information
Patent Citations
Composite reinforced type magnetostrictive composite material and method for manufacturing the same
JP2017163119A
Rubber composition, vulcanizate of the rubber composition, and molding
JP2021031516A
High weather resistant magnetic particle and its manufacturing method, and resin composition for rare earth-bond magnet using it
JP2005191426A